Backshore Sand Infiltration Characterization for The Sustainable Waterfront City Tourism Development at Balikpapan Bay, Indonesia - Totok Sulistyo; Sari Bahagiarti Kusumayudha; Tedy Agung Cahyadi; Reza Adhi Fajar; Mariatul Kiptiah; Desak Made Ristia Kartika (Indonesian Journal on Geoscience, 2026)
The researched area is the waterfront city of Balikpapan City, where the east and south coast areas have been developed as tourist destinations. The east coastline has an attractive view with its extensive sand deposits, geologically known as quaternary alluvium deposits (QA). On the south coastline, sands are spotted and have a limited spread with a steeper slope. The infiltration rate measurement and sampling were conducted in fifteen locations on the east coast and ten locations on the south coast to assess the water inundation potential on coastal sand. The field observation of water inundation after rain was also conducted to locate the inundation areas. The subtraction of two satellite images was also conducted for validation. Actual sand infiltration rates of the east and south coasts range from relatively slow to very fast. The impact of slow to medium infiltration is the surface water inundation that disturbs the function of the coastal sand as a place for tourist activities. Based on the overall infiltration, the East Coast has greater vulnerability to water inundation than the South Coast. The implication of such a condition without proper engineering treatment in the long term will reduce tourist visits. As a consequence, the revenue will decrease, and cause negative multiplier effects on the economy of local inhabitants. Scientific findings will contribute to the geoscience knowledge; the origin of the sand deposits determines the differences in the physical characteristics of the east and south coast sands. The source of the south coastline sand is the Tertiary Miocene Balikpapan Formation (Tmbp). Meanwhile, the source of the east coastline sands is the Tertiary Pliocene Kampungbaru Formation (Tpkb).